Model-based approach for specifying requirements of virtual reality software products - Karre, Sai Anirudh; Reddy, Y. Raghu (Frontiers in Virtual Reality, 2024)
Gathering requirements for developing Virtual Reality (VR) Software products is laborious.It requires detailed elicitation of scene flow, articles in the scene, action responses, custom behaviors, and timeline of events. The slightest change in requirements will escalate the design and development cost. While most VR practitioners depend on conventional software engineering (SE) requirement-gathering techniques, they desire novel methods to ease VR software development. With severe software platform fragmentation and volatility in hardware offerings, VR practitioners need assistance specifying non-volatile requirements for a minimum viable VR software product. To address this gap, we present a model-based tool called VReqST, a requirement specification tool for specifying requirements for developing Virtual Reality Software products. Using VReqST, requirement analysts can specify the requirements of simple to complex multi-scene VR software products and Virtual Environments (VE). VReqST is customizable and is competent in illustrating custom requirements for new locomotion, colocation, teleportation algorithms, etc. We worked with the VR community from Industry for adoption and feedback. We revised and included the desired features based on inputs from the VR community and gathered their observations on the overall impact of VReqST in practice.